Performance of Kharif Rice (Oryza sativa L.) under Different Nursery Densities and Plant Population - Pasha, Md. Latheef; Ramireddy, P. Raghu (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted at Agricultural Research Station, Kampasagar Nalgonda, Telangana during the kharif seasons of 2011 and 2012 to find out the effect of different nursery densities and plant population on grain yield and yield attributes in rice. Tiller number and panicle number m-2 were significantly higher at 44 hills m-2 plant population than 33 hills m-2 and 25 hills m-2. Panicle length, filled grains panicle-1 and 1000 grain weight were significantly not influenced with plant population. Though there was non significance difference of grain yield with different plant populations, adopting 44 hills m-2 recorded superior grain yield (5.39 t ha-1) over 33 (5.08 t ha-1 ) and 25 hills m-2 (4.95 t ha-1). Among nursery densities, 2.5, 5 and 7.5 kg seed 40 m-2 did not show any significant influence on yield attributes and grain yield. Numerically, higher grain yields were observed in 2.5 kg seed 40 m-2 (5.3 t ha-1) than 5 kg seed 40 m-2 (5.12 t ha-1) and 7.5 kg seed 40 m-2 (5.01 t ha-1).Nutrient uptake was higher in 44 hills m-2 than 33 and 25 hills m-2. NPK uptake was significantly higher at 2.5 kg seed 40 m-2 than 7.5 kg seed 40 m-2. Higher gross and net returns were earned in 44 hills m-2 (Rs. 80850 and Rs. 50325) than 25 hills m-2 (Rs. 74250 and Rs. 48750). 2.5 kg seed 40 m-2 recorded higher gross and net returns ( ` 79500 and Rs. 52640) than other seed densities.